PENGEMBANGAN DIGITAL MARKETING PADA UMKM ARTSYA LAUNDRY KOTA BATAM - Lady Lady; Antony Sentoso; Lina Lina; Lindawati Lindawati; Viviani Viviani; Joey Joey (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Digital marketing is marketing services or products using digital technology, especially in digital, this marketing can be done via cellphones, digital advertising, and other digital media. With digital marketing, people can get information and communication quickly and easily. This research uses a qualitative method in the form of a case study that focuses on an object with in-depth observation. This type of qualitative research data covers the opinions, characteristics, attitudes, and experiences of the informants on the object phenomenon. Through digital marketing, Artsya Laundry can reach consumers more broadly and effectively. By adopting digital marketing, Artsya Laundry can increase brand visibility, increase the number of customers, and expand market reach.